Architects of delusion : Europe, America, and the Iraq War - Serfaty, Simon (EBL-Schweitzer, 2008)
The commencement of war in Iraq in 2003 was met with a variety of reactions around the globe. In Architects of Delusion, Simon Serfaty presents a historical analysis of how and why the decision to wage war was endorsed by some of America's main European allies, especially Britain, and opposed by others, especially France and Germany. Tony Blair, George W. Bush, Jacques Chirac, and Gerhard Schroeder were, Serfaty argues, the architects of one of the most serious crises in postwar transatlantic relations. These four heads of state were the victims not only of their personal delusions but also of those of the nations they led. They all played the hand that their countries had dealt them--the forceful hand of a righteous America, the principled acquiescence of a faithful Britain, the determined intransigence of a quarrelsome France, and the ambiguous "new way" of a recast Germany. Serfaty's deft interweaving of the political histories and cultures of the four countries and the personalities of their leaders transcends the Europe-bashing debate sparked by the Iraq invasion. He contends that not one of these four leaders was entirely right or entirely wrong in his approach to the others or to the issues, before and during the war. For the resulting wounds to heal, though, and for the continuity of transatlantic relations, he reminds us that the United States and France must end their estrangement, France and Britain must resolve their differences, Germany must carry its weight relative to both France and Britain, and the United States must exert the same visionary leadership for the twenty-first century that it showed during its rise to preeminence in the twentieth century